Recovery of a Medieval Brucella melitensis Genome Using Shotgun Metagenomics - Kay, Gemma L.; Sergeant, Martin J.; Giuffra, Valentina; Bandiera, Pasquale; Milanese, Marco; Bramanti, Barbara; Bianucci, Raffaella; Pallen, Mark J. (mBio, 2014)
Shotgun metagenomics provides a powerful assumption-free approach to the recovery of pathogen genomes from contemporary and historical material. We sequenced the metagenome of a calcified nodule from the skeleton of a 14th-century middle-aged male excavated from the medieval Sardinian settlement of Geridu. We obtained 6.5-fold coverage of a Brucella melitensis genome. Sequence reads from this genome showed signatures typical of ancient or aged DNA. Despite the relatively low coverage, we were able to use information from single-nucleotide polymorphisms to place the medieval pathogen genome within a clade of B. melitensis strains that included the well-studied Ether strain and two other recent Italian isolates. We confirmed this placement using information from deletions and IS 711 insertions. We conclude that metagenomics stands ready to document past and present infections, shedding light on the emergence, evolution, and spread of microbial pathogens. IMPORTANCE Infectious diseases have shaped human populations and societies throughout history. The recovery of pathogen DNA sequences from human remains provides an opportunity to identify and characterize the causes of individual and epidemic infections. By sequencing DNA extracted from medieval human remains through shotgun metagenomics, without target-specific capture or amplification, we have obtained a draft genome sequence of an ~700-year-old Brucella melitensis strain. Using a variety of bioinformatic approaches, we have shown that this historical strain is most closely related to recent strains isolated from Italy, confirming the continuity of this zoonotic infection, and even a specific lineage, in the Mediterranean region over the centuries. Infectious diseases have shaped human populations and societies throughout history. The recovery of pathogen DNA sequences from human remains provides an opportunity to identify and characterize the causes of individual and epidemic infections. By sequencing DNA extracted from medieval human remains through shotgun metagenomics, without target-specific capture or amplification, we have obtained a draft genome sequence of an ~700-year-old Brucella melitensis strain. Using a variety of bioinformatic approaches, we have shown that this historical strain is most closely related to recent strains isolated from Italy, confirming the continuity of this zoonotic infection, and even a specific lineage, in the Mediterranean region over the centuries.